(untitled) (Medical Forum Monthly, 2020)
Objective: To know the efficacy of Danzen DS-added tamsulosin for expulsion of the symptomatic distal ureteral stones. Study Design: Descriptive, cross sectional study. Place and Duration of Study: This study was conducted at the Outpatient Department of Urology, Sheikh Zayed Hospital, Rahim Yar Khan, Pakistan from June 2016 to February 2017. Materials and Methods: Eighty-four male/female patients (aged:19-40 years) with single 5-9mm sized lower ureteral stone and colic pain for less than one month were registered using consecutive sampling technique. The subjects were advised to take 10mg tab Danzen DS thrice a day and 0.4mg cap tamsulosin (once a day) for maximum two weeks and visit hospital on 5th, 10th and 15th day for follow up including ultrasonography abdomen for stone positioning. Results: All the patients (N = 84) adhered with the therapy. The stone expelled in 61 (72.62%) subjects within average time of 11.5 days. Higher stone removal rate was recorded in males than females (75 vs. 68.76, respectively; p = 0.78). There was significant difference in the rate against stone size (75% for 5-7 and 61.36% for 8-9mm; p = 0.01). None of the patients reported significant adverse effects whereas episodes (1-3) of mild colic pain were documented against two participants. Conclusion: The Danzen DS-added tamsulosin combination therapy shows acceptable efficacy in terms of stone expulsion rate, management time, adverse effects, and episode of pain. The therapy can be used on large scale after validation.